Teaching humorous irony to L2 and heritage speakers of Spanish. (March 2022) - Shively, Rachel L.; Acevedo, Juan; Cano, Rocio; Etxeberria-Ortego, Izadi
The present study examined the effect of a pedagogical intervention about humorous verbal irony in Spanish with a mixed group of 40 second language (L2) and heritage speakers of Spanish. Unlike previous studies that have considered only irony comprehension, this project incorporated both comprehension and production of irony into instruction and assessment. The intervention consisted of 2.5 hours of lessons that focused on humorous irony and irony cues. To assess effectiveness, participants completed a pretest and posttest of an irony comprehension instrument and a written production questionnaire designed to elicit humorous irony. The results from the study indicate that the intervention was beneficial in increasing participants' accurate interpretation of irony and identification of tone of voice as an irony cue. Additionally, after instruction, participants produced significantly more irony and incorporated new resources into their ironic responses. However, participants did not increase their success in being humorous over time. No significant group differences were observed, suggesting that the instruction had similar effects for both L2 and heritage speakers.